The Potential Role Of STK11 as a Biomarker for Intestinal Cancer - Mahdi, Zena Abdul-Ameer; Albaidhani, Farqad A.; Oudah, Noor Abdulameer (Jour Med Resh and Health Sci, 2024)
Colorectal and small intestinal cancers together still pose a serious threat to world health. The necessity for trustworthy biomarkers is highlighted by the fact that early diagnosis is critical to better patient outcomes. In this regard, the serine/threonine kinase 11 (STK11) has come to light as a possible option. The STK11 gene codes for the serine/threonine kinase liver kinase B1 (LKB1), which is essential for preserving cellular polarity, adhesion, and metabolism. LKB1 inactivation is a frequent occurrence in many tumors, especially those that affect the gastrointestinal tract. The biological roles of STK11/LKB1 and its numerous contributions to the onset and spread of gastrointestinal cancer are reviewed in this study. This review addresses the role that STK11/LKB1 plays in the AMP-activated protein kinase (AMPK) pathway, which is a master regulator of cellular energy balance. Also, review how LKB1 regulates important signaling pathways, such as Wnt/?-catenin, PI3K/AKT/mTOR network, and how LKB1 depletion causes these pathways to become dysregulated, which in turn promotes cancer. It investigates the relationship between some gastrointestinal malignancies, such as Peutz-Jeghers syndrome, gastric cancer, and colorectal cancer, and LKB1 mutations. Lastly, we discuss the possible therapeutic implication of LKB1 signaling targeting in the management of gastrointestinal cancer.